DISTIBUTION OF ENTEROPATHOGENS ASSOCIATED WITH DIARRHOEA AMONG INFANTS AND CHILDREN OF HIGH AND LOW SOCIO-ECONOMIC CLASSES - K. Badalian; F. Sheiban; R. Nategh; M. Asgari; K. nafici; S. Shahid (Tehran University of Medical Sciences, 1975)
Bacteriologic, parasitic, fungal and viral investigation of stools of 268 sick and 105 healthy infants and children during a two-year period from March 1970, through March 1972, revealed that: Shigella and Salmonella are still the major causes of infantile endemic diarrhea in Tehran. Enteropathogenic bacteria were isolated from 26.86% of sick vs 7.61% healthy children. Salmonella Typhimurium was found to be the most common enterobacterial pathogen in young sick children of the low social class, whereas in the sick children of high class, Shigella was the most prevalent organism and Shigella sonnei the predominant serotype. Cases of diarrhea due to EPEC and Salmonella other than Sal. Typhimurium occurred mainly in the high socioeconomic class in this age group.